One little room - McDonald, Peter 1962- (Carcanet Poetry, 2024)
"The poems in 'One Little Room' enter and explore confined spaces in history and personal memory. The spaces prove not to be as small as they seem from the outside: they expand and interconnect to produce new and dazzling perspectives out of the limits of concentrated meditation and formal shape alike"
Keywords: Belfast (Northern Ireland) / Poetry; Emerson, Ralph Waldo / 1803-1882 / Poetry; Bible / Psalms / Poetry